RODELS OF LEARNING THE BASICS OF INFORMATICS IN PRIMARY SCHOOLS AND THE MEANS OF THEIR IMPLEMENTATION - V. P. Tataurov (Kherson State University, 2013)
The article provides a model of learning the basics of informatics in primary school. The question of the selection and application of hardware and software implementation of these models in teaching the subject "Steps to informatics." The basic requirements for the selection of hardware and software.